Transcriptome analysis reveals the accelerated expression of genes related to photosynthesis and chlorophyll biosynthesis contribution to shade-tolerant in Phoebe bournei - Jing An; Xiaoli Wei; Honghao Huo (BMC Plant Biology, 2022)
Abstract Background Phoebe bournei (P. bournei) is an important and endemic wood species in China. However, the plantation, nursing, and preservation of P. bournei are often affected by light. To investigate its physiological changes and molecular mechanism of low light tolerance, two-year-old P. bournei seedlings were subjected to different shading conditions. With the increase of light intensity in the shade, the leaf color of P. bournei seedlings became darkened, the aboveground/underground biomass significantly increased, the content of chlorophyll increased and the net photosynthetic rate significantly increased. Results de novo transcriptome analysis showed that 724 and 3,248 genes were differentially expressed due to low light intensity at T1 (35% light exposure) and T2 (10% light exposure), respectively, when compared to the controls. Furthermore, the differentially expressed genes (DEGs) were implicated in photosynthesis, nitrogen metabolism, plant hormone signal transduction, biosynthesis of secondary metabolites, and protein processing in the endoplasmic reticulum by functional enrichment analysis. Moreover, the expression of HSP, CAB, HEMA1, GSA, DVR, MYB, bHLH, PORA, CAO, GLK, and photosystem I and II complex-related genes significantly increased after low light exposure at T2 and T1. Conclusions The present study suggests that the rapid growth of P. bournei seedlings under shading conditions may be the result of the accelerated expression of genes related to photosynthesis and chlorophyll biosynthesis, which enable plants to maintain a high photosynthesis rate even under low light conditions.